(untitled) (Mongolian Journal of International Affairs, 2024)
The Third Neighbor Policy is a strategic foreign policy approach adopted by Mongolia to diversify its international partnerships beyond its immediate neighbors, China and Russia. This policy aims to enhance Mongolia’s economic, political, and security ties with countries outside its immediate region, reducing dependence on neighboring giants and enhancing strategic autonomy. The United States has become an important "third neighbor" for Mongolia, with the two countries establishing a strategic partnership focusing on areas such as trade, clean energy, and aviation. While there are similarities and differences in the implementation of the Third Neighbor Policy by other countries, Mongolia should continue to pursue this approach in the future to enhance its strategic autonomy. The policy holds promising future opportunities for Mongolia to expand cooperation in various sectors, particularly in terms of economic cooperation.